(untitled) (Annals of Medical Research, 2021)
Aim: Scabies is a contagious parasitic skin disorder, which is characterized by severe pruritus. Scabies usually presents with papules and excoriations on hands, feet, axillae, umbilicus and genitalia. Recently, both increased prevalence of the disease and resistance to anti-scabies treatment have been reported. Therefore, early diagnosis and appropriate treatment of scabies are crucial. The aim of this study was to evaluate the characteristics of patients with scabies and treatments that the patients received in order to provide successful management of scabies.Material and Methods: Medical records of the patients who were diagnosed with scabies between June 2019 and February 2020 were reviewed retrospectively. Age, gender, disease duration, similar symptoms in household members, dermatological examination, prior treatments and treatments that we recommended were recorded.Results: The study included 74 patients (39 female, 35 male) with scabies. The mean age of the patients was 40.6±16.7 years. The mean disease duration was 53.5±5.5 days. Pruritus was observed in the household members of 37 (50%) patients. 18 (24.3%) patients received only symptomatic treatment since they were diagnosed as other pruritic dermatoses including xerosis or dermatitis, previously. However, we treated 58 (78.4%) patients using topical permethrin 5%. In addition, 4 (5.4%) patients were treated with topical sulfur 12.5% and 3 (4.1%) patients were treated with balsam of Peru. 9 (12.2%) patients who were resistant to topical treatment received oral ivermectin for complete cure of scabies. Conclusion: The results indicated that most of the patients with scabies (78.4%) were treated with topical permethrin successfully, whereas 12.2% patients required oral ivermectin in addition to topical anti-scabies treatment. Nevertheless, delay in diagnosis of 24.3% patients might increase the risk of spread of scabies. Therefore, we recommend topical permethrin, oral ivermectin and immediate further clinical and laboratory evaluation for indeterminate cases.